(1 ) -2*3*(-4) (2) -6*(-5)*(-7)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 01:33:27
(1)-2*3*(-4)(2)-6*(-5)*(-7)(1)-2*3*(-4)(2)-6*(-5)*(-7)(1)-2*3*(-4)(2)-6*(-5)*(-7)(1)-2*3*(4)=-(2*3)*
(1 ) -2*3*(-4) (2) -6*(-5)*(-7)
(1 ) -2*3*(-4) (2) -6*(-5)*(-7)
(1 ) -2*3*(-4) (2) -6*(-5)*(-7)
(1) -2*3*(4)
=-(2*3)*(-4)
=(-6)*(-4)
=24 (负负得正,即负数乘负数等于正数)
(2) -6*(-5)*(-7)
=30*(-7) (负负得正)
=-210 (正负得负,即正数乘负数等于负数)
1()2()3()4
(1) (2) (3) (4) (5)
1)2)3)4)5)
1) 2) 3) 4) 5)
1 2 3 4 ()
0-(+2/1)-(+5/2)-(-4/3)-(+4/1)-(-5/3)
计算(1)(2)(3)(4)题,
(1)、(2)、(3)、(4).
6.(1)、(2)、(3)、(4)
19 (1).(2).(3).(4)
(2)(3)(4)化简,(1)计算
(1)、(2)、(3)、(4)题对吗?
第六题(1)(2)(3)(4)
-1-(-2)-(+3)+(-4)-(-5)
填空(1)、(2)、(3)、(4)
(1)、(2)、(3)、(4)题谢谢
(1)(2)(3)(4)怎么写
8(1)(2)(3)(4)